Kampanye Teknologi yang Ramah Perempuan - Sujianto, Agus Eko (Musawa Jurnal Studi Gender dan Islam, 2007)
This article is developed from the Beijing Declaration and Platf orm for Action held in 1995. The fourth Woman World Summit results in 12 critical sectors that have to be the focus and be the strategic outlook for the governments, international communities and public societies including non-government organizations and private sectors to implement. the Declaration. One of the critical issues is the movement of women, especially the sixth section of the Declaration which concerned with women and technology. This section describes four strategic issues: one of them is to conduct a women~friendly technology campaign. The reality shows that women's involvement in technology (this article focuses on informational technology) is till limited. Even in the developed country, far example in the United States of America it still receives a gradual slowdown.